PENAMBAHAN PERYSARATAN PADA TENDER PEKERJAAN KONSTRUKSI DITINJAU DARI HUKUM PERSAINGAN USAHA - Bintang Puwan Permata (Fakultas Hukum Universitas Sebelas Maret, 2024)
Procurement of goods and services should be carried out with the spirit of creating fair competition and should involve as many business entities as possible with equivalent classifications and types of businesses. Additional requirements in construction job tenders are typically motivated by the client's desire to secure credible and quality suppliers of goods/services. However, these reasons are often exploited by procurement actors to favor suppliers with specific relationships, thereby undermining fair competition. This article aims to examine provisions related to additional requirements in construction job tenders. It is a normative legal research using legislative and theoretical approaches. Secondary data in the form of legal materials will be analyzed using deductive reasoning. The conclusion drawn from this article is that adding requirements such as the provision of material supplier endorsements in construction tenders violates principles of fair competition if such endorsements steer towards only one specific factory/distributor